Solve for y -3(y-6)=-2y+20

Math
-3(y-6)=-2y+20
Simplify -3(y-6).
Tap for more steps…
Apply the distributive property.
-3y-3⋅-6=-2y+20
Multiply -3 by -6.
-3y+18=-2y+20
-3y+18=-2y+20
Move all terms containing y to the left side of the equation.
Tap for more steps…
Add 2y to both sides of the equation.
-3y+18+2y=20
Add -3y and 2y.
-y+18=20
-y+18=20
Move all terms not containing y to the right side of the equation.
Tap for more steps…
Subtract 18 from both sides of the equation.
-y=20-18
Subtract 18 from 20.
-y=2
-y=2
Multiply each term in -y=2 by -1
Tap for more steps…
Multiply each term in -y=2 by -1.
(-y)⋅-1=2⋅-1
Multiply (-y)⋅-1.
Tap for more steps…
Multiply -1 by -1.
1y=2⋅-1
Multiply y by 1.
y=2⋅-1
y=2⋅-1
Multiply 2 by -1.
y=-2
y=-2
Solve for y -3(y-6)=-2y+20

Meet the Team our Math Expers

Our Professionals

Robert Kristofer

Anna Frok

Magnus Flores

Lydia Fran

We are MathExperts

Solve all your Math Problems: https://elanyachtselection.com/

We can solve all your math problems
Scroll to top